1997
DOI: 10.1038/sj.cdd.4400270
|View full text |Cite
|
Sign up to set email alerts
|

Presence of a functional vitamin D receptor does not correlate with vitamin D3 phenotypic effects in myeloid differentiation

Abstract: Although VDR is expressed in all the acute myeloid leukemia cell populations studied, most of these leukemias do not exibit any phenotypic response when exposed to VD. To determine whether VD resistance is related to an altered VDR function, we performed an analysis of VDR expression, phosphorylation, DNA binding capacity and transactivation activity in several leukemic myeloid cell lines arrested at different levels of maturation. Our results indicate that VD induces a clear phenotypic effect, i.e. terminal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 50 publications
0
15
1
Order By: Relevance
“…7,8 This property, referred to as 'lineage switching' or 'intrahematopoietic plasticity', was initially based on the observation that a number of leukemic cell lines undergo phenotypic changes 'in vitro' as a result of specific manipulations such as pharmacological treatments 9,10 or transcription factor overexpression. 11,12 Further reports have subsequently indicated that trans-differentiation processes can be reproduced by using normal CD34 þ -derived myeloid precursors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,8 This property, referred to as 'lineage switching' or 'intrahematopoietic plasticity', was initially based on the observation that a number of leukemic cell lines undergo phenotypic changes 'in vitro' as a result of specific manipulations such as pharmacological treatments 9,10 or transcription factor overexpression. 11,12 Further reports have subsequently indicated that trans-differentiation processes can be reproduced by using normal CD34 þ -derived myeloid precursors.…”
Section: Discussionmentioning
confidence: 99%
“…Although this model would imply a univocal fate for a cell that has been already committed to a precise maturation lineage, several reports indicate that hematopoietic precursors are able to transdifferentiate from a lineage to another. 7,8 This biological property of hematopoietic cells, referred to as 'lineage switching' or 'intrahematopoietic plasticity', is essentially based on the observation that a number of leukemic cell lines undergo phenotypic changes 'in vitro' as a result of specific manipulations, such as pharmacological treatments 9,10 and transcription factors overexpression. 11,12 By using this approach, lineage switches between erythroid and myeloid, megakaryocytic and erythroid, or even lymphoid and myeloid cell compartments have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis is also supported by the already reported observation that early leukemic myeloblasts express functional vitamin D3 receptors (VDR), but are unable to differentiate after treatment with VD. 49 Apart from RARa, other transcription factors, such as PU.1, AML1 and C/EBPa, are involved in the regulation of myeloid differentiation. 4 Furthermore, several transcription regulatory elements, including the RAREs, have been shown to lie inside the promoter region of certain myeloid related genes, allowing to hypothesize that the expression of such genes is cooperatively activated by the interested transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…12 In leukaemic cells RXR also forms heterodimers with the vitamin D receptor (VDR). 29 VDR ligation induces CD11b expression in U937 cells. 30 Specific effects of KH1060 in VDR pathways are not yet characterised.…”
Section: Figurementioning
confidence: 97%